Effectiveness and characteristics of atmospheric CO2 removal in croplands via enhanced weathering of industrial Ca-rich silicate byproducts - Yoshioka, Rina; Nakamura, Kengo; Sekiai, Ryota; Wang, Jiajie; Watanabe, Noriaki (Frontiers in Environmental Science, 2022)
Enhanced weathering of industrial Ca-rich silicate byproducts in croplands is potentially profitable for large-scale atmospheric CO2 removal; during the weathering process, CO2 dissolves to form HCO3− and CO32− in alkaline soil pore water, which eventually flows into the ocean. However, the effectiveness of such systems is still in doubt, owing to the unrealistic models used for prediction and the insufficient consideration of the dynamic influences of soils on fluid chemistry. We determined the effectiveness of such systems for atmospheric CO2 removal, along with their characteristics, through a set of batch- and flow-through-type laboratory experiments, using andosol and decomposed granite soil as agricultural and non-agricultural soils, respectively, and Portland cement, steelmaking slag, and coal fly ash as industrial byproducts. The results of the batch-type experiments demonstrated that agricultural soils were suitable for CO2 removal, owing to their moderately high pH and Ca concentrations in pore water that prevented intensive calcium carbonate precipitation. The flow-through experiments demonstrated that a higher Ca-content byproduct can have a large atmospheric CO2 removal capacity. However, the magnitude of CO2 removal and its time-dependent behavior were difficult to predict because they were not in conjunction with the changes in the average pH value. This indicated that the diffusive transport of CO2 from the atmosphere-soil interface to deeper soils was more complex than expected. Maximizing CO2 removal requires a better understanding of the diffusive transport of CO2 through gas-filled pore spaces, created by unsteady-state air–water two-phase flow, due to intermittent rainfall.